2020
DOI: 10.3390/soilsystems4020030
|View full text |Cite
|
Sign up to set email alerts
|

Streambank Legacy Sediments in Surface Waters: Phosphorus Sources or Sinks?

Abstract: Streambank legacy sediments can contribute substantial amounts of sediments to Mid-Atlantic waterways. However, there is uncertainty about the sediment-bound P inputs and the fate of legacy sediment P in surface waters. We compared legacy sediment P concentrations against other streambank sediments and upland soils and evaluated a variety of P indices to determine if legacy sediments are a source or sink of P to surface waters. Legacy sediments were collected from 15 streambanks in the mid-Atlantic USA. Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Perturbations of sediment and nutrients to stream networks significantly impact hydrologic, biological, and chemical functions in downstream aquatic and riparian environments (Graeber et al, 2012;Inamdar et al, 2012;Walter et al, 2007). Thus, quantification of physical and chemical consequences of legacy sediment influx, including volumes of eroded soil/sediment and associated nutrients, will improve our understanding and modeling of nutrient pollution in Piedmont streams and reservoirs (Inamdar et al, 2020(Inamdar et al, , 2021. Moreover, determining sediment and nutrient volumes is an essential constraint in ongoing efforts to reduce the contributions of non-point source nutrient loading to the eutrophication of rivers and estuaries along the Atlantic coast (e.g., Bhattacharya & Osburn, 2020;Fleming et al, 2019;Lebo et al, 2012;Paerl, 2009;Paerl et al, 2010).…”
Section: Anthropogenic Impacts On Hillslope Erosionmentioning
confidence: 99%
“…Perturbations of sediment and nutrients to stream networks significantly impact hydrologic, biological, and chemical functions in downstream aquatic and riparian environments (Graeber et al, 2012;Inamdar et al, 2012;Walter et al, 2007). Thus, quantification of physical and chemical consequences of legacy sediment influx, including volumes of eroded soil/sediment and associated nutrients, will improve our understanding and modeling of nutrient pollution in Piedmont streams and reservoirs (Inamdar et al, 2020(Inamdar et al, , 2021. Moreover, determining sediment and nutrient volumes is an essential constraint in ongoing efforts to reduce the contributions of non-point source nutrient loading to the eutrophication of rivers and estuaries along the Atlantic coast (e.g., Bhattacharya & Osburn, 2020;Fleming et al, 2019;Lebo et al, 2012;Paerl, 2009;Paerl et al, 2010).…”
Section: Anthropogenic Impacts On Hillslope Erosionmentioning
confidence: 99%
“…Microbial activities and their underlying ecosystem functions such as denitrification also occur in streambank sediments (Koval, 2011;Sienkiewicz et al, 2020;Weitzman et al, 2014). In general, microbial distribution and functional gene profiles vary with sites and depth, and the balance of nutrient processes (e.g., related to nitrogen [N] or phosphorus [P]) determines whether the riparian zone acts as a sink or as a source of nutrients (Inamdar et al, 2020;Weitzman & Kaye, 2017). Microbial distribution and N cycling genes are also influenced by land use and environmental conditions (Sienkiewicz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Prevailing theory is that P is retained within the stream during low flows and suddenly remobilized during high flows, especially for point-source-affected reaches (Demars et al, 2005;Jarvie et al, 2011Jarvie et al, , 2012Sharpley et al, 2013). Field studies have observed that (a) large amounts of legacy P can accumulate within streambeds (Lannergård et al, 2020;McCallister & Logan, 1978;McDaniel et al, 2009), (b) P retention and remobilization can be highly spatially variable (Casillas-Ituarte et al, 2020;Inamdar et al, 2020), and (c) P retention and remobilization can be highly temporally variable (Jarvie et al, 2005(Jarvie et al, , 2006. To capture these dynamics, a watershed model must explicitly track in-stream P stores and simulate the processes by which P is retained and remobilized.…”
Section: Introductionmentioning
confidence: 99%